Association of Increased Circulating Acetic Acid With Poor Survival in Pseudomonas aeruginosa Ventilator-Associated Pneumonia Patients - Qi, Xiaoling; Zhang, Li; Xu, Jing; Tao, Zheying; Wang, Xiaoli; Qiu, Yuzhen; Pan, Tingting; Liu, Zhaojun; Qu, Hongping; Tan, Ruoming; Liu, Jialin (Frontiers in Cellular and Infection Microbiology, 2021)
Background We previously found that microbial disruption in Pseudomonas aeruginosa ventilator-associated pneumonia (PA-VAP) patients are long-lasting. Long-term microbial dysbiosis may lead to changes in metabolites. Short-chain fatty acids (SCFAs) are microbial fermentation products and show beneficial effects in patients with pneumonia. In this study, we aimed to explore the association between circulating SCFA levels and clinical outcomes in patients with PA-VAP. Methods In this study, we analyzed SCFAs in the serum of 49 patients with PA-VAP by gas chromatography-mass spectrometry analysis. Twenty of these patients died, and 29 survived. The correlation between serum SCFAs and patient survival and immune parameters was analyzed. Results We developed a partial least squares discriminant analysis (PLS-DA) model to examine differential SCFAs in 49 patients with PA-VAP. Among the seven SCFAs, only acetic acid was increased in non-survivors (P = 0.031, VIP > 1). Furthermore, high levels of acetic acid (>1.96ug/ml) showed increased 90-day mortality compared to low levels of acetic acid (<1.96ug/ml) in Kaplan-Meier survival analyses (P = 0.027). Increased acetic acid also correlated with reduced circulating lymphocyte and monocyte counts. Conclusion Our study showed that increased circulating acetic acid is associated with 90-day mortality in PA-VAP patients. The decrease in lymphocytes and monocytes might be affected by acetic acid and involved in the poor prognosis.